Indigenous peoples’ voices and engagement on climate change: towards improved health and wellbeing - Lansbury, Nina; Mosby, Vinnitta; Creamer, Sandra J.; Moggridge, Bradley; Evans, Geoffrey R.; Pecl, Gretta; Ireland, Lillian (Frontiers in Climate, 2025)
Western climate science largely fails to value, engage with and apply Indigenous Knowledges in a meaningful way. Here, we explore the ways in which the current gap in Indigenous Knowledges and representation in climate research can be addressed. A rapid review of relevant literature and grey materials was conducted to identify how Aboriginal and Torres Strait Islander Peoples, and the essential Knowledges they hold, should and will inform and direct climate change research. This timely review of academic and grey literature to inform a wider public conversation of Indigenous leadership, voices and participation in climate change discussions, in and beyond the Intergovernmental Panel on Climate Change (IPCC) process, both in Australia and with consequences internationally.